Iron metabolism and resistance to infection by invasive bacteria in the social amoeba Dictyostelium discoideum - Bozzaro, Salvatore; Buracco, Simona; Peracino, Barbara (Frontiers in Cellular and Infection Microbiology, 2013)
Dictyostelium cells are forest soil amoebae, which feed on bacteria and proliferate as solitary cells until bacteria are consumed. Starvation triggers a change in life style, forcing cells to gather into aggregates to form multicellular organisms capable of cell differentiation and morphogenesis. As a soil amoeba and a phagocyte that grazes on bacteria as the obligate source of food, Dictyostelium could be a natural host of pathogenic bacteria. Indeed, many pathogens that occasionally infect humans are hosted for most of their time in protozoa or free-living amoebae, where evolution of their virulence traits occurs. Due to these features and its amenability to genetic manipulation, Dictyostelium has become a valuable model organism for studying strategies of both the host to resist infection and the pathogen to escape the defense mechanisms. Similarly to higher eukaryotes, iron homeostasis is crucial for Dictyostelium resistance to invasive bacteria. Iron is essential for Dictyostelium, as both iron deficiency or overload inhibit cell growth. The Dictyostelium genome shares with mammals many genes regulating iron homeostasis. Iron transporters of the Nramp (Slc11A) family are represented with two genes, encoding Nramp1 and Nramp2. Like the mammalian ortholog, Nramp1 is recruited to phagosomes and macropinosomes, whereas Nramp2 is a membrane protein of the contractile vacuole network, which regulates osmolarity. Nramp1 and Nramp2 localization in distinct compartments suggests that both proteins synergistically regulate iron homeostasis. Rather than by absorption via membrane transporters, iron is likely gained by degradation of ingested bacteria and efflux via Nramp1 from phagosomes to the cytosol. Nramp gene disruption increases Dictyostelium sensitivity to infection, enhancing intracellular growth of Legionella or Mycobacteria. Generation of mutants in other “iron genes” will help identify genes essential for iron homeostasis and resistance to pathogens.